Supra‐annular valve strategy for an early degenerated transcatheter balloon‐expandable heart valve. Issue 7 (23rd January 2018) - Kamioka, Norihiko; Caughron, Hope; Corrigan, Frank; Block, Peter; Babaliaros, Vasilis
Abstract: Currently, there are no recommendations regarding the selection of valve type for a transcatheter heart valve (THV)‐in‐THV procedure. A supra‐annular valve design may be superior in that it results in a larger effective orifice area and may have a lower chance of valve thrombosis after THV‐in‐THV. In this report, we describe the use of a supra‐annular valve strategy for an early degenerated THV.